A Working Model of Slump and Recovery from Disturbances to Capital-Goods Demand in an Open Nonmonetary Economy - Phelps, Edmund S. (American Economic Review, 1988)
This paper is one in a series directed toward the construction, with certain modern building blocks, of a non-monetary theory of employment fluctuation in market economies. The closed-economy model here parallels the open-economy model in Phelps (1988). The objective is a plausible theory that helps to account for some or all of the long swings in economic activity over recent decades. In fact, this non-monetary theory has grown out of one of the models used by Fitoussi and Phelps (1988) to account for the 1980s depression over much of the world, a slump that demand-driven models are hard-pressed to explain.